Final answer:
To find |r - s|, we need to subtract the magnitudes of r and s and find the absolute value of the result. The expression representing |r - s| is √((3√(3) + 11√(2))^2 + (3 - 11√(2))^2).
Step-by-step explanation:
To find |r - s|, we need to subtract the magnitudes of r and s and find the absolute value of the result. Given that |r| = 6 at an angle of 30° and |s| = 11 at an angle of 225°, we can use the formula |r - s| = √((|r|cos(angle of r) - |s|cos(angle of s))^2 + (|r|sin(angle of r) - |s|sin(angle of s))^2).
Substituting the given values, we get |r - s| = √((6cos(30°) - 11cos(225°))^2 + (6sin(30°) - 11sin(225°))^2).
Simplifying further, |r - s| = √((6*√(3)/2 - 11*(-√(2)/√(2)))^2 + (6*1/2 - 11*(-√(2)/√(2)))^2).
Finally, |r - s| = √((3√(3) + 11√(2))^2 + (3 - 11√(2))^2). This is the expression representing |r - s|.